Extracellular matrix degradation pathways and fatty acid metabolism regulate distinct pulmonary vascular cell types in pulmonary arterial hypertension. (1st March 2021) - Mumby, Sharon; Perros, F.; Hui, C.; Xu, B.L.; Xu, W.; Elyasigomari, V; Hautefort, A.; Manaud, G.; Humbert, M.; Chung, K.F.; Wort, S.J.; Adcock, I.M.
Abstract : Pulmonary arterial hypertension describes a group of diseases characterised by raised pulmonary vascular resistance, resulting from vascular remodelling in the pre‐capillary resistance arterioles. Left untreated, patients die from right heart failure. Pulmonary vascular remodelling involves all cell types but to date the precise roles of the different cells is unknown. This study investigated differences in basal gene expression between pulmonary arterial hypertension and controls using both human pulmonary microvascular endothelial cells and human pulmonary artery smooth muscle cells. Human pulmonary microvascular endothelial cells and human pulmonary artery smooth muscle cells from pulmonary arterial hypertension patients and controls were cultured to confluence, harvested and RNA extracted. Whole genome sequencing was performed and after transcript quantification and normalisation, we examined differentially expressed genes and applied gene set enrichment analysis to the differentially expressed genes to identify putative activated pathways. Human pulmonary microvascular endothelial cells displayed 1008 significant ( p  ≤ 0.0001) differentially expressed genes in pulmonary arterial hypertension samples compared to controls. In human pulmonary artery smooth muscle cells, there were 229 significant ( p  ≤ 0.0001) differentially expressed genes between pulmonary arterial hypertension and controls. Pathway analysis revealed distinctive differences: human pulmonary microvascular endothelial cells display down‐regulation of extracellular matrix organisation, collagen formation and biosynthesis, focal‐ and cell‐adhesion molecules suggesting severe endothelial barrier dysfunction and vascular permeability in pulmonary arterial hypertension pathogenesis. In contrast, pathways in human pulmonary artery smooth muscle cells were mainly up‐regulated, including those for fatty acid metabolism, biosynthesis of unsaturated fatty acids, cell–cell and adherens junction interactions suggesting a more energy‐driven proliferative phenotype. This suggests that the two cell types play different mechanistic roles in pulmonary arterial hypertension pathogenesis and further studies are required to fully elucidate the role each plays and the interactions between these cell types in vascular remodelling in disease progression.